Nitrogen‐Doped Porous Graphene Coated with Fe3O4 Nanoparticles for Advanced Supercapacitor Electrode Material with Improved Electrochemical Performance. (27th February 2020) - Su, Siyu; Lin, Yueming; Dai, Huimin; Lai, Liuqin; Zhu, Xiaohong
Abstract: With the increasing demand for high‐performance energy storage devices, single materials of ordinary structures for electrode materials have become increasingly difficult to meet people's needs. Therefore, composites of inimitable structures have drawn considerable attention. In this work, nitrogen‐doped porous graphene coated with Fe3 O4 nanoparticles (NPGF) is prepared by an efficient and green pyrolysis method. Structural and compositional characterizations confirm that the NPGF nanohybrids possess uniformly distributed pore structure and quite pure composition which is free of any impurities. In addition, electrochemical characterization verifies the excellent electrochemical performance, such as high‐specific capacitance (713 F g −1 at 1 A g −1 ), prominent rate capability (capacitance retention of 77.3% and 67.9% when the current density is increased respectively from 1 to 10 and 20 A g −1 ), and outstanding cycling stability (capacitance retention of 94.3% after 3000 cycles). Such promising results suggest that the NPGF nanohybrids have great application prospects in future high‐performance supercapacitors. Abstract : Nitrogen‐doped porous graphene coated with Fe3 O4 nanoparticles is successfully prepared by a green and low‐cost method. Electrochemical tests confirm that this material has excellent electrochemical properties, which are higher than those reported in most of the existing literature. Therefore, a series of characterization methods are used to analyze the origin of its high performance.